Monoclonal Purified F VIII for Continuous Infusion: Stability, Microbiological Safety and Clinical Experience - Schulman, S; Varon, D; Keller, N; Gitel, S; Martinowitz, U (Thrombosis and Haemostasis, 1994)
Replacement therapy for patients with hemophilia A postoperatively or for major hemorrhage, administered as a continuous infusion, is efficient and reduces the requirement for factor VIII (F VIII). The convenience of the method is increased by using a minipump and not diluting the concentrate further after reconstitution. A monoclonally purified F VIII concentrate (Monoclate-P®), was evaluated for its stability after reconstitution in different infusion systems, for its microbiological safety as well as clinical safety and efficacy in continuous infusion. The F VIII activity was unaffected by 2 of the 3 infusion systems at room temperature during 15 days, whereas in the third (CADD®-1) it decreased below 80% of initial value after 3-7 days. Addition of heparin (1 U/ml) or low molecular weight heparin (1 anti-Xa U/ml), which are used to prevent thrombophlebitis at the site of infusion, did not affect the stability. Nine out of 9 samples taken from the infusion systems after 3 days and again after 7 days were sterile. After inoculation with Staphylococcus aureus or Escherichia coli the bacterial growth in samples of the reconstitued concentrate was not different from that in lidocain in saline or heparin in saline. F VIII was given in continuous infusion with a minipump (Infu-Med™) to 12 patients undergoing major surgery and 8 patients with major hemorrhage for a total of 157 days. A progressive decrease of the clearance was seen during the first 5 days of infusion from 3.0 to 1.7 ml/kg/h. Hemostasis was effectively achieved, and no infectious complications were registered. The administration of monoclonally purified F VIII with a minipump is safe, efficient and convenient and reduces the consumption of F VIII when high doses are needed. Some patients can be discharged earlier and admission to the hospital may even be unnecessary, since high and steady F VIII levels can be maintained.